Day 2 Wed, October 16, 2019 2019
DOI: 10.2118/196588-ms
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Simplified Local Density Theory and Molecular Dynamics Simulation to Study the Local Density Distribution of Hydrocarbon Gas in Shale Gas Reservoir

Abstract: The density distribution of hydrocarbon molecules in Nano-pore media affects the storage of gas, particular for shale reservoir which contains rich organic matters. The density distribution can reveal the adsorption effect which is related to the gas storage mechanism. In literature, researchers proposed using local density theory such as Lennard Jones Potential in lieu of molecular dynamics (MD) simulation and laboratory measurement because of its high computation performance. Core sample study shows that man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Moreover, these simulations can compute a wide range of macroscopic physical properties. MD simulations offer distinct advantages, particularly in situations in which experimental replication would be challenging or impossible, such as ultra-high pressure and temperature conditions [20][21][22][23], studies of fluid confinement behavior [24][25][26], investigations at the nanoscale interface [27][28][29][30], and examinations of complex molecular interactions [31][32][33].…”
Section: Asphalt Models and Simulation Detailsmentioning
confidence: 99%
“…Moreover, these simulations can compute a wide range of macroscopic physical properties. MD simulations offer distinct advantages, particularly in situations in which experimental replication would be challenging or impossible, such as ultra-high pressure and temperature conditions [20][21][22][23], studies of fluid confinement behavior [24][25][26], investigations at the nanoscale interface [27][28][29][30], and examinations of complex molecular interactions [31][32][33].…”
Section: Asphalt Models and Simulation Detailsmentioning
confidence: 99%
“…Through recent years, extensive studies have been conducted to research different aspects of shale reservoirs. From one perspective, extensive experimental and mathematical works have been dedicated to study a fine-detailed physical mechanism observed in the shale reservoir, such as the water flowback phenomenon [2,3], and molecular dynamics, such as adsorption and phase behavior [4][5][6][7][8]. From another perspective, great efforts have also been focused on the macroscale analysis of different modelling workflows and various data sources such as microseismic and geomechanics [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%